Soil Acidobacterial community composition changes sensitively with wetland degradation in northeastern of China - Sui, Xin; Frey, Beat; Yang, Libin; Liu, Yingnan; Zhang, Rongtao; Ni, Hongwei; Li, Mai-He (Frontiers in Microbiology, 2022)
Acidobacteria are a major component of the soil bacteria and are conducted for many soil functions, and the soil acidobacterial structure and diversity are affected by climate changes and human activities. However, soil acidobacterial structure and diversity in wetland ecosystems are still limited recognized. The current study aimed to study the acidobacterial community and diversity in relation to soil environmental factors along a typical degradation series from primitive wetland to forest in a representative fresh wetland in northeastern China. The Shannon diversity index of soil acidobacteria changed significantly between different degradation stages (P < 0.05). The most abundant subgroups of acidobacteria accounted for 31% (Gp1), 5% (Gp2), 12% (Gp3), 2% (Gp4), 5% (Gp6) and 2% (Gp7) in soils within five successional series. The compositions of soil acidobacteria in wetland stages were significantly affected by soil moisture content, soil total nitrogen and available nitrogen contents, while those in forest stages were significantly driven by soil pH, soil organic carbon, total nitrogen, available phosphorus and soil moisture content. Our results indicated that the soil acidobacterial community were mainly structured by both soil physicochemical parameters and vegetation composition, and wetland degradation towards forests will greatly influence the soil acidobacterial structureand thus the wetland functions.